Ionic liquid additive for improving stability of hard carbon negative electrode interface of sodium-ion battery and application of ionic liquid additive
By introducing pyrrolidin type double cationic liquid as an electrolyte additive to form a stable SEI film, the problem of reduced capacity and poor stability of sodium ion batteries after multiple cycles is solved, and the long cycle stability and capacity retention rate of the battery are significantly improved.
Patent Information
- Application Number
- CN202411579221.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-07
AI Technical Summary
After multiple charge and discharge cycles, the capacity of existing sodium ion batteries has significantly reduced and poor circulation stability, resulting in a gradual weakening of energy storage capacity and rapid decline in performance.
The pyrrolidin type double cationic liquid is introduced as an electrolyte additive, forming a tighter ion pair through interaction with Na+, destroying the original solvated structure, and promoting the formation of a stable solid electrolyte interface (SEI) film.
It significantly improves the long cycle stability of sodium ion batteries, maintains high capacity and performance, and even after multiple charge and discharge cycles, the capacity retention rate reaches 90.4%, and extends the cycle life of the battery.
Smart Images

Figure CN119581660A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to an ionic liquid additive for improving the interface stability of a hard carbon negative electrode of a sodium ion battery and an application thereof. Background Art
[0002] In the wave of energy revolution in the 21st century, electrochemical energy storage technology, as a key link in promoting the transformation of energy structure and realizing the popularization of clean energy, has received widespread attention from the world. As a potential electrochemical energy storage device, sodium-ion batteries have become an important supplement and development direction of lithium batteries due to their advantages of abundant resources, low cost and environmental protection. In the research and development of sodium-ion batteries, the selection and optimization of anode materials play a vital role in improving the overall performance of batteries and promoting their commercialization process. As one of the anode materials of sodium-ion batteries, hard carbon (HC) can reversibly store sodium ions due to its unique structure and performance characteristics, providing a specific capacity of up to 250-320mAh / g.
[0003] However, after multiple charge and discharge cycles, batteries prepared under existing technology usually have a significant reduction in capacity or poor cycle stability. This indicates that the energy storage capacity of these batteries will gradually weaken during long-term use and cannot maintain the initial high capacity state. At the same time, their cycle life is also affected, resulting in rapid performance degradation, making it difficult to meet long-term, high-efficiency energy supply needs. Summary of the invention
[0004] In order to comprehensively solve the above problems, the present invention proposes an effective method of adjusting the electrolyte components or introducing additives. Ionic liquids are ideal alternative organic solvents or electrolyte additives for improving the safety and stability of sodium ion batteries due to their unique properties, low melting point, high thermal and chemical stability, strong ionic conductivity and wide electrochemical window. Therefore, the present invention applies ionic liquids to the electrolyte of sodium ion batteries to solve the problem of poor stability of hard carbon negative electrodes.
[0005] In order to achieve the above object, the first aspect of the present invention provides an ionic liquid additive for improving the interfacial stability of a hard carbon negative electrode of a sodium ion battery, wherein the structure of the ionic liquid additive is:
[0006]
[0007] Wherein, 1≤n≤10; R is any one of methyl, ethyl or butyl; anion B- is PF6 - TFSI - 、FSI - or BF4 - Any one of .
[0008] A second aspect of the present invention provides an application of an ionic liquid additive for improving the interfacial stability of a hard carbon negative electrode of a sodium ion battery, wherein the ionic liquid additive is used for preparing an electrolyte.
[0009] Preferably, the electrolyte comprises an electrolyte salt, an ionic liquid additive and an organic solvent;
[0010] The electrolyte salt is a sodium salt, the ionic liquid additive is a pyrrolidine type dicationic liquid, and the organic solvent is a mixed carbonate or a single ether solvent, wherein the carbonate is a mixture of one or two or three.
[0011] Preferably, the ionic liquid additive is C2di[mPy].di[B], C4di[mPy].di[B], C6di[mPy].di[B] or C 10 Any one of di[mPy].di[B], where B is any one of PF6, TFSI, FSI or BF4.
[0012] Preferably, the carbonate solvent is a mixture of any two or three of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate;
[0013] The ether solvent is any one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.
[0014] Preferably, the concentration of the electrolyte salt is 0.5 to 3 mol / L; the mass of the ionic liquid additive is 1% to 10% of the total mass of the electrolyte.
[0015] Preferably, when carbonate solvents are mixed, the volume ratio is 1:(0.5-2):(0-2).
[0016] A third aspect of the present invention provides an application of an electrolyte prepared by the above method, wherein the electrolyte is used to prepare a sodium ion battery, wherein the negative electrode material of the sodium ion battery is hard carbon.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. The present invention uses pyrrolidine dicationic ionic liquid as an electrolyte additive. Since the ionic liquid has high thermal stability, high ionic conductivity and good chemical stability, when the ionic liquid additive is introduced into the electrolyte, the anions contained in it may react with Na + This interaction may be due to the special structure or charge distribution of the anion, which enhances its interaction with Na + In pure solvent, Na +Usually surrounded by solvent molecules, forming a solvation shell. The introduction of ionic liquid additives will destroy this original solvation structure. On the one hand, the anions in the additives may react with Na + Combine to form a tighter ion pair, thereby reducing Na + Contact with solvent molecules; on the other hand, cations may also interact with solvent molecules, further changing the solvation environment. 2+ As a compound with a lower LUMO (lowest unoccupied molecular orbital) energy level, it is more susceptible to reduction reactions during battery charging and discharging. 2+ When reduced, a stable, thin, and NaF-rich solid electrolyte interface (SEI) film is generated. As an important interface layer between the battery negative electrode and the electrolyte, the SEI film can effectively prevent the electrolyte from directly contacting the negative electrode material, thereby inhibiting unnecessary chemical reactions. The stable SEI film significantly improves the long-cycle stability of the battery because it effectively reduces the capacity decay during the charge and discharge process.
[0019] The present invention significantly improves the long-cycle stability of the battery by introducing ionic liquid additives and forming a stable SEI film. Even after multiple charge and discharge cycles, the battery can still maintain a high capacity and performance.
[0020] 2. The electrolyte prepared based on the ionic liquid additive proposed in the present invention is applied to the Na||HC half-cell. The capacity retention rate after 400 cycles at a current density of 100 mA / g reaches 90.4%, and the capacity retention rate after 500 cycles at a current density of 300 mA / g reaches 81%. In addition, the cycle stability of the NVP||HC battery is also improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The cycle diagram of the Na||HC half-cell obtained by preparing the electrolyte in Example 1;
[0022] Figure 2 The cycle diagram of the Na||HC half-cell obtained by preparing the electrolyte in Example 2;
[0023] Figure 3 The cycle diagram of the Na||HC half-cell obtained by preparing the electrolyte in Example 3;
[0024] Figure 4 The cycle diagram of the Na||HC half-cell obtained by preparing the electrolyte in Example 4;
[0025] Figure 5 Performance diagram of Na||HC half-cell obtained by preparing electrolyte in Example 5;
[0026] Figure 6Performance diagram of Na||HC half-cell obtained by preparing electrolyte in Example 6;
[0027] Figure 7 Performance diagram of Na||HC half-cell obtained by preparing electrolyte in Example 7;
[0028] Figure 8 Performance diagram of Na||HC half-cell obtained by preparing electrolyte in Example 8;
[0029] Fig. 9 Performance diagram of Na||HC half-cell obtained by preparing electrolyte in Example 9;
[0030] Fig.10 Performance diagram of Na||HC half-cell obtained by preparing electrolyte in Example 10;
[0031] Fig.11 Performance diagram of Na||HC half-cell obtained by preparing electrolyte in Example 11;
[0032] Fig.12 Performance diagram of Na||HC half-cell obtained by preparing electrolyte in Example 12;
[0033] Fig.13 Performance diagram of Na||HC half-cell obtained by preparing electrolyte in Example 13;
[0034] Fig.14 Performance diagram of Na||HC half-cell obtained by preparing electrolyte in Example 14;
[0035] Fig.15 Performance diagram of Na||HC half-cell obtained by preparing electrolyte in Example 15;
[0036] Fig.16 Performance diagram of Na||HC half-cell obtained by preparing electrolyte in Example 16;
[0037] Fig.17 Performance diagram of Na||HC half-cell obtained by preparing electrolyte in Example 17;
[0038] Fig.18 Performance diagram of Na||HC half-cell obtained by preparing electrolyte in Example 18;
[0039] Fig.19 Performance diagram of Na||HC half-cell obtained by preparing electrolyte in Comparative Example 1;
[0040] Fig. 20 Performance diagram of Na||HC half-cell obtained by preparing electrolyte in Comparative Example 2;
[0041] Fig.21The cycle diagram of the full battery obtained by preparing the electrolyte in Comparative Example 1;
[0042] Fig. 22 The cycle diagram of the full battery obtained by preparing the electrolyte in Example 2;
[0043] Fig.23 The cycle diagram of the full battery obtained by preparing the electrolyte in Example 3;
[0044] Fig.24 The cycle diagram of the full battery obtained by preparing the electrolyte in Example 5;
[0045] Fig.25 The cycle diagram of the full battery obtained by preparing the electrolyte in Example 14; DETAILED DESCRIPTION
[0046] The following embodiments and the accompanying Figure 1-Figure 25 To further illustrate the present invention, it should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0047] An ionic liquid additive for improving the interfacial stability of a hard carbon negative electrode of a sodium ion battery, wherein the ionic liquid additive has a structure of:
[0048]
[0049] Wherein, 1≤n≤10; R is any one of methyl, ethyl or butyl; anion B - PF6 - , TFSI-, FSI- or BF4 - Any one of .
[0050] An application of an ionic liquid additive for improving the interface stability of a hard carbon negative electrode of a sodium ion battery, and the use of the ionic liquid additive for preparing an electrolyte.
[0051] The electrolyte comprises an electrolyte salt, an ionic liquid additive and an organic solvent;
[0052] The electrolyte salt is a sodium salt, the ionic liquid additive is a pyrrolidine type dicationic liquid, and the organic solvent is a mixed carbonate or a single ether solvent, wherein the carbonate is a mixture of one or two or three.
[0053] The sodium salt is any one of NaPF6, NaTFSI, NaFSI, and NaBF4.
[0054] The ionic liquid additive is C2di[mPy].di[B], C4di[mPy].di[B], C6di[mPy].di[B] or C 10Any one of di[mPy].di[B], where B is any one of PF6, TFSI, FSI or BF4.
[0055] The carbonate solvent is a mixture of any two or three of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC);
[0056] The ether solvent is any one of ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (DEGDME), and tetraethylene glycol dimethyl ether (TEGDME).
[0057] The concentration of the electrolyte salt is 0.5 to 3 mol / L. The mass of the ionic liquid additive is 1% to 10% of the total mass of the electrolyte.
[0058] The mixing volume ratio of the organic solvent is 1:(0.5-2):(0-2).
[0059] When carbonate solvents are mixed, they can be a single type, a mixture of two types, or a mixture of three types, and the volume ratio is 1:(0.5-2):(0-2).
[0060] A method for preparing an electrolyte based on an ionic liquid additive having enhanced interface stability of a hard carbon negative electrode of a sodium ion battery, wherein a sodium salt, an ionic liquid additive and an organic solvent are mixed to obtain an electrolyte;
[0061] The electrolyte salt is a sodium salt, the ionic liquid additive is a pyrrolidine type dicationic liquid, and the organic solvent is one of a carbonate solvent or an ether solvent or a mixture of the two.
[0062] The electrolyte prepared by the above method is used to prepare a sodium ion battery. The sodium ion battery includes an electrolyte, a positive electrode and a negative electrode.
[0063] The negative electrode material of the sodium ion battery is hard carbon, and the negative electrode layer also includes a binder and a conductive agent.
[0064] Preferably, the binder includes at least one of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), and polyacrylic acid (PAA). The conductive agent includes at least one of acetylene black and super carbon black (Super-P). The mass ratio of the hard carbon material, the binder, and the conductive agent is (100-ab):a:b, where a=b=5-10. Preferably, the conductive current collector includes: aluminum foil, carbon-coated aluminum foil, and copper foil.
[0065] The positive electrode includes: a positive electrode material, a binder and a conductive agent. The positive electrode material includes at least one of sodium vanadium phosphate (NVP), sodium ferric pyrophosphate (NFPP), and sodium ferric sulfate (Na2Fe(SO4)2). The binder includes at least one of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR). The conductive agent includes at least one of acetylene black, Super-P, and Ketjen black. The mass ratio of the positive electrode material, the binder, and the conductive agent is (100-xy):x:y, where x=y=4-10. The positive electrode current collector includes at least one of aluminum foil, copper foil, and carbon-coated aluminum foil. In the half-cell, the positive electrode is a sodium sheet.
[0066] Embodiment 1:
[0067] In this embodiment 1, a button-type sodium battery hard carbon half-cell is taken as an example, and the specific preparation scheme is as follows:
[0068] (1) In a glove box filled with high-purity argon (water content <0.1 ppm, oxygen content <0.1 ppm), ethylene carbonate (EC) and dimethyl carbonate (DMC) were uniformly mixed at a volume ratio of EC:DMC=1:1, and water was removed by molecular sieve to obtain a mixed organic solvent;
[0069] (2) Also in the glove box, add electrolyte salt NaPF6 to the above mixed solvent and shake evenly. The concentration is 1M (mol / L) to obtain a basic electrolyte solution;
[0070] (3) Add the ionic liquid additive C4di[mPy].di[PF6] to the basic electrolyte obtained in step (2), and mix evenly until the liquid is clear and transparent. The ionic liquid additive accounts for 1% of the total electrolyte mass. After standing for one hour, a sodium ion battery electrolyte suitable for hard carbon negative electrode is obtained.
[0071] Example 2-18
[0072] The sodium ion battery and its compatible electrolyte were prepared by referring to the method of Example 1. The other steps were the same as those of Example 1, except for the selection and proportion of the sodium salt, solvent component and ionic liquid additive in the electrolyte. The sodium ion battery electrolyte formulas in Examples 2-18 are shown in Table 1 below.
[0073] Comparative Example 1:
[0074] The difference from Example 1 is that the electrolyte contains only sodium salt and organic solvent, and no ionic liquid additive is added. The other steps are the same as in Example 1.
[0075] Comparative Example 2:
[0076] The difference from Example 1 is that the organic solvent in the electrolyte is ether dimethyl ether (DME), and no ionic liquid additive is included. The other steps are the same as those in Example 1.
[0077] Table 1 Formula of sodium ion battery electrolyte in Examples 1-18 and Comparative Examples 1-2
[0078] Sodium salt (M) Organic solvents Additives (wt%) Example 1 <![CDATA[1MNaPF6]]> EC:DMC=1:1 <![CDATA[1wt%C4di[mPy].di[PF6]]]> Example 2 <![CDATA[1MNaPF6]]> EC:DMC=1:1 <![CDATA[2wt%C4di[mPy].di[PF6]]]> Example 3 <![CDATA[1MNaPF6]]> EC:DMC=1:1 <![CDATA[5wt%C4di[mPy].di[PF6]]]> Example 4 <![CDATA[1MNaPF6]]> EC:DMC:EMC=1:1:1 <![CDATA[1wt%C4di[mPy].di[PF6]]]> Example 5 <![CDATA[1MNaPF6]]> EC:DMC:EMC=1:2:2 <![CDATA[5wt%C4di[mPy].di[PF6]]]> Example 6 <![CDATA[1MNaPF6]]> EC:DMC:PC=1:1:1 <![CDATA[2wt%C4di[mPy].di[PF6]]]> Example 7 <![CDATA[1MNaPF6]]> EC:PC=1:1 <![CDATA[5wt%C4di[mPy].di[PF6]]]> Example 8 <![CDATA[1MNaPF6]]> EC:DEC=1:1 <![CDATA[1wt%C4di[mPy].di[PF6]]]> Example 9 1MNaFSI EC:DMC=1:1 <![CDATA[2wt%C4di[mPy].di[FSI]]]> Example 10 <![CDATA[1MNaPF6]]> DME <![CDATA[2wt%C4di[mPy].di[PF6]]]> Embodiment 11 1MNaFSI EC:DMC=1:1 <![CDATA[1wt%C2di[mPy].di[FSI]]]> Example 12 1MNaFSI EC:DMC:EMC=1:1:1 <![CDATA[5wt%C6di[mPy].di[FSI]]]> Embodiment 13 <![CDATA[1MNaPF6]]> DEGDME <![CDATA[1wt%C4di[mPy].di[PF6]]]> Embodiment 14 <![CDATA[2MNaPF6]]> EC:DMC=1:1 <![CDATA[2wt%C4di[mPy].di[PF6]]]> Embodiment 15 <![CDATA[1MNaPF6]]> TEGDME <![CDATA[10wt%C2di[mPy].di[PF6]]]> Example 16 <![CDATA[1MNaBF4]]> EC:DMC=1:1 <![CDATA[5wt%C 10 at[mPy].at[BF4]]]> Embodiment 17 <![CDATA[1MNaPF6]]> EC:DMC:DEC=1:1:1 <![CDATA[1wt%C4di[mPy].di[PF6]]]> Embodiment 18 1MNaTFSI EC:DMC=1:1 <![CDATA[2wt%C6di[mPy].di[TFSI]]]> Comparative Example 1 <![CDATA[1MNaPF6]]> EC:DMC=1:1 / Comparative Example 2 <![CDATA[1MNaPF6]]> DME /
[0079] experiment:
[0080] The performance test of the sodium ion battery electrolyte prepared in the above embodiments and comparative examples was completed through the following experiments.
[0081] 1. Preparation of Sodium Ion Half-Cell
[0082] After mixing hard carbon material (Japan Kuraray), binder (PVDF), and conductive agent (acetylene black) at a mass ratio of 90:5:5, N-methylpyrrolidone (NMP) was added and ground evenly to prepare slurry, which was then coated on aluminum foil and placed in a vacuum drying oven at 110° for 12 hours. The negative electrode was cut into a circular negative electrode sheet with a diameter of 12 mm.
[0083] In a glove box filled with high-purity argon, a button sodium half-cell was assembled in the following order: battery negative electrode shell, sodium sheet, electrolyte (50 μL), diaphragm, electrolyte (75 μL), electrode sheet, gasket, spring, and positive electrode shell.
[0084] The preparation method of sodium ion full battery is as follows:
[0085] The preparation of the negative electrode is the same as that of the electrode of the above half-cell. The preparation of the positive electrode includes:
[0086] After mixing the positive electrode material, binder (PVDF), and conductive agent (Super-P) at a mass ratio of 80:10:10, add N-methylpyrrolidone (NMP), grind evenly to prepare slurry, then coat the slurry on aluminum foil and place it in a vacuum drying oven at 110° for 12 hours. Cut into circular pole pieces with a diameter of 12 mm.
[0087] In a glove box filled with high-purity argon, a button-type sodium-ion full battery was assembled in the order of battery negative electrode shell, negative electrode sheet, electrolyte (50 μL), diaphragm, electrolyte (50 μL), positive electrode sheet, gasket, shrapnel, and positive electrode shell.
[0088] 2. Test Method
[0089] 2.1 Cycle test:
[0090] At 25°C, the sodium ion battery was charged and discharged at a constant current density of 15 mA / g. After 10 cycles of activation, the cycle test was performed at a current density of 100 mA / g. The voltage range was 0.01 to 2 V.
[0091] 2.2 Long cycle test:
[0092] At 25°C, the sodium ion battery was charged and discharged at a constant current density of 30 mA / g. After activation for 3 cycles, a long cycle test was performed at a current density of 300 mA / g. The voltage range was 0.01 to 2 V.
[0093] 2.3 Full battery cycle test:
[0094] The positive and negative electrodes were assembled into half-cells, with sodium electrolyte as the negative electrode and the electrode as the positive electrode. They were charged and discharged at a current density of 20 mA / g, activated for 5 cycles, and then disassembled the half-cells and reassembled into full cells in a glove box filled with pure argon (water < 0.1 ppm, oxygen < 0.1 ppm), activated for 3 cycles at 0.1 C current, and then cycled at 1 C current.
[0095] 3. Test results
[0096] Table 2 below shows the performance and cycle test results of the sodium half-cells of Examples 1-18 and Comparative Examples 1-2.
[0097] Table 2 Performance and cycle test results of sodium half-cells of Examples 1-18 and Comparative Examples 1-2
[0098]
[0099] The performance tests of the batteries of Examples 1 to 18 and Comparative Examples 1 to 2 were performed at a current density of 15 mA / g. The cycle test was performed by first cycling 10 cycles at a current density of 15 mA / g and then cycling 400 cycles at a current density of 100 mA / g to obtain the capacity retention rate in the Na||HC half-cell.
[0100] Table 3 Cyclic test results of sodium battery of Examples 1-18 and Comparative Example 1
[0101] Cathode Materials Reversible capacity (mAh / g) Capacity retention rate (%) Example 2 NVP 95.8 88.4 Example 3 NVP 110.8 88.4 Embodiment 14 NFPP 88.29 82.7 Embodiment 15 NFPP 106.75 85.1 Comparative Example 1 NVP 91.3 6
[0102] The cycle test of the above-mentioned embodiment and comparative example full battery was first activated for 3 cycles with a current of 0.1C, and then cycled 300 times with a current of 1C to obtain the capacity retention rate in the sodium battery. Wherein, when the negative electrode material of the full battery is hard carbon and the positive electrode material is NVP, the voltage range of the full battery test is 2.2 to 3.7V; when the positive electrode material is NFPP, the voltage range of the full battery test is 2 to 4.2V.
[0103] In summary, the present invention uses pyrrolidine dicationic ionic liquid as an additive for sodium ion battery electrolyte, and systematically studies its effect on the cycle performance of Na||HC half-cell and full-cell, especially the effect on the long-cycle stability of hard carbon negative electrode in Na||HC half-cell.
[0104] Compared with the electrolyte without ionic liquid, after adding the additive, the hard carbon negative electrode showed higher stability during the cycle and the battery decay rate was significantly reduced. This is mainly attributed to the fact that the ionic liquid additive can promote the formation of a thin and stable SEI film, inhibit the occurrence of side reactions on the surface of the hard carbon negative electrode, thereby reducing the capacity decay during the cycle. It can also effectively inhibit the volume expansion of the hard carbon negative electrode, which further extends the cycle life of the battery.
[0105] The results show that the Na||HC half-cell and full-cell assembled with the electrolyte prepared with the dicationic ionic liquid additive provided by the present invention can significantly improve the long-cycle stability. After the Na||HC half-cell was cycled 400 times at a current density of 100 mA / g, the capacity retention rate reached 90.4%.
[0106] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. An ionic liquid additive for improving the interfacial stability of a hard carbon negative electrode of a sodium ion battery, characterized in that: The structure of the ionic liquid additive is: Wherein, 1≤n≤10; R is any one of methyl, ethyl or butyl; anion B - PF6 - TFSI - 、FSI - or BF4 - Any one of .
2. The use of an ionic liquid additive for improving the interfacial stability of a hard carbon negative electrode of a sodium ion battery according to claim 1, characterized in that: Used for preparing electrolyte.
3. The use of an ionic liquid additive for improving the interfacial stability of a hard carbon negative electrode of a sodium ion battery according to claim 2, characterized in that: The electrolyte comprises an electrolyte salt, an ionic liquid additive and an organic solvent; The electrolyte salt is a sodium salt, the ionic liquid additive is a pyrrolidine type dicationic liquid, and the organic solvent is a mixed carbonate or a single ether solvent, wherein the carbonate is a mixture of one or two or three.
4. The use of an ionic liquid additive for improving the interfacial stability of a hard carbon negative electrode of a sodium ion battery according to claim 3, characterized in that: The sodium salt is any one of NaPF6, NaTFSI, NaFSI, and NaBF4.
5. The use of an ionic liquid additive for improving the interfacial stability of a hard carbon negative electrode of a sodium ion battery according to claim 4, characterized in that: The ionic liquid additive is C2di[mPy].di[B], C4di[mPy].di[B], C6di[mPy].di[B] or C 10 Any one of di[mPy].di[B], where B is any one of PF6, TFSI, FSI or BF4.
6. The use of an ionic liquid additive for improving the interfacial stability of a hard carbon negative electrode of a sodium ion battery according to claim 5, characterized in that: The carbonate solvent is a mixture of any two or three of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; The ether solvent is any one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.
7. The use of an ionic liquid additive for improving the interfacial stability of a hard carbon negative electrode of a sodium ion battery according to claim 6, characterized in that: The concentration of the electrolyte salt is 0.5-3 mol / L; the mass of the ionic liquid additive is 1%-10% of the total mass of the electrolyte.
8. The use of an ionic liquid additive for improving the interfacial stability of a hard carbon negative electrode of a sodium ion battery according to claim 7, characterized in that: When carbonate solvents are mixed, the volume ratio is 1:(0.5-2):(0-2).
9. Use of the electrolyte prepared by the method according to any one of claims 2 to 8, characterized in that: Used for preparing sodium ion batteries, wherein the negative electrode material of the sodium ion battery is hard carbon.